Application of Discovery Learning Model with Concrete Materials to Improve Natural Science Learning Outcomes to The Theme Heat and Its Transfer For The Fifth Grade Students of SDN 1 Karangsari in Academic Year of 2019/2020 - Asih Fitria Janti; Suhartono Suhartono; Wahyudi Wahyudi (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The purpose of this study are (1) describing the application of Discovery Learning model with concrete materials, (2) improving natural science learning outcomes, (3) describing problems and solution. It is a collaborative classroom action research conducted in three cycles. The subjects are teacher and students. Research data are qualitative and quantitative. Data collection techniques are nontest and tests. Data analysis includes data reduction, data presentation, and conclusions. The results show that: (1) the steps to the application of discovery learning model with concrete materials are providing stimulation, identification problems, collecting data, processing data, proof, and drawing conclusions; (2) the application of discovery learning model with concrete materials can improve natural sciences learning outcomes. It is proven by the average percentage of teacher= 89.39%, students' observations= 86.75%, and research evaluation= 91.18%; (3) the problems found in this study are students fail in constructing hypotheses, teacher does not prove hypotheses, some student are passive in learning process, teacher only chooses active students, students ask the teacher in less polite. The solutions are the teacher assists the students to construct hypotheses according, the teacher proves the hypotheses, the teacher gives motivation, the teacher chooses active and passive students, the teacher asks the students to speak well.